MORINGA LEAVES AND BANANA BLOSSOM ON BREAST MILK PRODUCTION IN POSTPARTUM MOTHERS : AN EXPERIMENTAL STUDY - Putri Wahyu Wigati; Dhita Kris Prasetyanti; Sutrisni; Halimatus Saidah; Galuh Pradian Yanuaringsih (Universitas Kadiri, 2026)
Inadequate breast milk production remains a common problem among postpartum mothers and may affect exclusive breastfeeding practices. Although moringa leaves and banana blossom have been traditionally used as natural galactagogues, evidence regarding their combined effect on breast milk production remains limited. This study aimed to analyze the effect of moringa oleifera leaves and banana blossom consumption on breast milk production among postpartum mothers in the working area of Ngasem Public Health Center, Kediri Regency, Indonesia. A pre-experimental one-group pretest–posttest design was conducted involving 15 postpartum mothers selected using purposive sampling. Breast milk production was assessed before and after the intervention using an observation checklist. Data were analyzed using the Wilcoxon Signed Rank Test with a significance level of 0.05. The findings showed that breast milk production improved after the intervention, with 86.7% of respondents demonstrating adequate milk production. Statistical analysis indicated a significant difference before and after intervention (p=0.003). Consumption of moringa leaves and banana blossom may improve breast milk production among postpartum mothers and could be considered a low-cost complementary nutritional intervention to support breastfeeding programs.